Aegyptiaca Romana : nilotic scenes and the Roman views of Egypt - Versluys, M. J. (Religions in the Graeco-Roman World, 2002)
This archaeological study investigates the meaning of the Egyptian and egyptianising artefacts that have been preserved from the Roman world in different ways. Its point of departure is a detailed study on the so-called Nilotic scenes or Nilotic landscapes. The book presents a comprehensive and illustrated catalogue of the genre that was popular all around the Mediterranean from the Hellenistic period to the Christian era as well as a contextualisation and interpretation. Drawing on the conclusions thus reached the whole group of Aegyptiaca Romana is subsequently studied. Based on a general overview of this material in the Roman world and, moreover, a case-study of the Aegyptiaca from the city of Rome the different meanings of this cultural phenomenon are mapped. Together with other Egyptian deities popular in the Roman world, the goddess Isis plays an important role in this discussion. Aegyptiaca Romana, among them the Nilotic scenes, are part of the reflection of the Roman attitude towards and thoughts on Egypt, Egyptian culture and the East. The concluding part of the book illustrates and tries to explain this Roman discourse on Egypt.